2021
DOI: 10.22141/2224-0713.8.110.2019.187888
|View full text |Cite
|
Sign up to set email alerts
|

Наслідки Таламічних Інсультів: Проспективне Клінічне Когортне Дослідження

Abstract: Background. Stroke is the second-leading global cause of death behind heart disease, accounting for 11.8 % of total deaths worldwide. However, currently, there are not enough published prospective hospital-based cohort studies that report and analyze outcomes of thalamic stroke. The purpose of this study is to determine the features of acute thalamic stroke outcomes in a prospective hospital-based cohort study, providing a comprehensive clinical and neuroimaging analysis of the treatment results and assessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Symptoms of thalamic syndrome might appear as sensory abnormalities, movement difficulties, dysesthesia, thalamic pain syndrome, and cognitive and emotional changes [ 11 ]. The diagnosis of thalamic syndrome involves a thorough neurological examination and imaging studies (such as magnetic resonance imaging or computed tomography scans) to determine the extent and cause of the thalamic damage [ 6 , 7 ]. The clinical findings in our patient corroborate the aforementioned findings with an unknown aetiology of the infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of thalamic syndrome might appear as sensory abnormalities, movement difficulties, dysesthesia, thalamic pain syndrome, and cognitive and emotional changes [ 11 ]. The diagnosis of thalamic syndrome involves a thorough neurological examination and imaging studies (such as magnetic resonance imaging or computed tomography scans) to determine the extent and cause of the thalamic damage [ 6 , 7 ]. The clinical findings in our patient corroborate the aforementioned findings with an unknown aetiology of the infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The thalamus is vital in sensory functions and the normal functioning of motor and cognitive systems which maintains light, temperature, pain, and touch sensitivity in our body along with the management of the informational flow in motor, visual, and auditory channels [ 6 ]. Clinical diagnosis is confirmed by physicians' evaluation of neuropsychological and neurological aspects in cases of thalamic strokes [ 7 ]. In this case report, we have highlighted thalamic syndrome in an elderly patient who presented with thalamic syndrome due to methylcobalamin deficiency, which has not been reported earlier.…”
Section: Introductionmentioning
confidence: 99%
“…The methods of the study, inclusion, and exclusion criteria have been reported in detail previously. [11,12] In brief, only MRI/CT-proven acute thalamic stroke patients age 18 years or older were included in this prospective, hospital-based, cohort study of acute thalamic stroke patients. Institutional ethics board approval was obtained and written informed consent received from all participants or legally authorized representative.…”
Section: Methodsmentioning
confidence: 99%
“…[10,11] However, currently, there are not enough published prospective hospital-based cohort studies that report and analyze pathophysiological features and patterns of the occurrence of neurological, neuropsychological, and clinical vascular syndromes of the thalamic stroke in the classical vascular territories, and their topical diagnosis using clinical, neurological, and neuroimaging methods in a prospective hospital-based cohort study. [10][11][12]…”
Section: Introductionmentioning
confidence: 99%